A Romance of Business: Genre, Scarcity, and the Businessman in the American Economic Novel - Jason Douglas (Belphégor)
The subtitle of Richard Kimball’s novel, Undercurrents of Wall Street, represents the central tension of the American business novel that emerges during the second half of the nineteenth century. The novel calls itself as a “romance of business.” As a romance, there is never any doubt that the story must restore the fortunes lost by the main character when his business fails. As a business narrative, a large part of the text explores the myriad ways in which market conditions prevent his return to profitability. The tension between the desire to make him a wealthy man and the difficulty of making him a successful businessman is the kind of tension that becomes the defining feature of the business novel. These novels, as economic narratives, have a logical commitment to market and resource constraints. But as novels, such texts are also committed to reinforcing the relationship between moral behavior and personal success. These novels reflect a dramatic shift in the conceptual landscape that transformed economics from a science of wealth to a science of scarcity. This conceptual shift is reflected in the structural reorganization of the business world to favor a new class of professional managers. The businessman becomes an important financial technology as well as the central element of economic narratives. The economic novel must be understood as an attempt to reconcile the mathematics and calculation of economics as a rising science of scarcity with the genre constraints of the American romance.